School Entrepreneurship through STEM PjBL Learning in Aquaponic Fish and Vegetable Farming Using Renewable Energy - Nurlaela Nurlaela; Rahmatia Thahir; Nurul Magfirah; Ahmad Swandi; Sri Rahmadhanningsih (SWAGATI : Journal of Community Service, 2026)
This Community Partnership Empowerment Program aims to enhance the capacity of science teachers and junior high school students in Pangkajene and Islands Regency through the implementation of STEM Project-Based Learning (PjBL) using a solar-powered aquaponics system. The program addresses two main problems: teachers’ limited ability to design innovative and integrative science learning and the underdeveloped school-based entrepreneurship education. The project was implemented at SMPN 1 Bungoro through five stages: socialization, training, technology implementation, mentoring and evaluation, and sustainability planning. The training results indicated a significant improvement in teachers’ understanding, with an N-Gain score of 0.70 (high category). Moreover, a school entrepreneurship unit was established utilizing an aquaponics system with a capacity of 100 net pots and 300 catfish, powered entirely by solar energy. The program not only produced tangible outputs such as vegetables and fish but also fostered environmental awareness, self-reliance, and managerial skills among participants. Overall, this program serves as a contextual learning model integrating science, technology, entrepreneurship, and renewable energy, while strengthening school–community partnerships to promote sustainable education and local economic resilience.